Inhibition of carrageenan induced inflammation in the rat knee joint by substance P antagonist. Issue 11 (November 1989) - Lam, F Y; Ferrell, W R
Abstract : The pathophysiology of acute joint inflammation remains unclear. Evidence is available to suggest a neurally mediated component to the inflammatory process. Acute joint inflammation in the rat knee, induced by intra-articular injection of 2% carrageenan, was reduced by 44% in animals whose knee had previously been injected with 1% capsaicin, while chronic joint denervation produced a 37% reduction. These results indicate a significant neurogenic component in this model of acute joint inflammation. Substance P may be the mediator of this response as intra-articular injection of this agent provoked an acute inflammatory response. Pretreatment of the test knee with the substance P antagonist d-Pro4, d-Trp7 9 10-SP(4-11), however, resulted in a 93% reduction of the inflammatory response to carrageenan. This unexpectedly large effect suggests that this substance P antagonist blocks both neurogenic and non-neurogenic mediators of inflammation. Sympathetic efferent fibres innervating the knee joint were not found to contribute to the neurogenic component of the inflammatory process.